Community Empowerment in PT. Indonesia Power's Corporate Social Responsibility (CSR) Program in the Alam Malon Batik Village Semarang - Garda Try Ananda; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
The problem of poverty in Indonesia is a social problem that is relevant forcontinuous review and a solution is sought. Symptoms of poverty are increasing in line with the multidimensional crisis faced by Indonesia. Empowerment of village communities is an alternative in reducing poverty. In the Empowerment Program, cooperation from all stakeholders from the government, private sector and other institutions is needed. Private sector is obliged to contribute to the environment. Through the Corporate Social Responsibility Program, one of them is through community empowerment. One of the factors that support the success or failure of an empowerment program is social capital, with good social capital, undoubtedly the goal of empowermentcan be easily achieved. PT. Indonesia Power has conducted its Corporate SocialResponsibility program in Kampung Alam Malon through the Sentra Batik VillageProgram.In this study carried out using a descriptive qualitative research approach.Qualitative methods are used by the author to assess the image produced from the CSRactivities program. This study focuses on community empowerment activities run bycompanies, namely CSR programs aimed at contributing to society and the environmentand improving the economy and the welfare of the community.The results of this study found that the empowerment program was not maximalin the welfare of the community because of the lack of the role of social capital bridgingand social capital linking in the implementation of empowerment programs. this resultedin a high level of public interest in the beginning of the program along with theempowerment program.Key Word : Community Empowerment, Corporate Social Responsibility, SocialCapital